2021
DOI: 10.3390/tropicalmed6020077
|View full text |Cite
|
Sign up to set email alerts
|

National Antibiotic Consumption for Human Use in Sierra Leone (2017–2019): A Cross-Sectional Study

Abstract: Monitoring antibiotic consumption is crucial to tackling antimicrobial resistance. However, currently there is no system in Sierra Leone for recording and reporting on antibiotic consumption. We therefore conducted a cross-sectional study to assess national antibiotic consumption expressed as defined daily dose (DDD) per 1000 inhabitants per day using all registered and imported antibiotics (categorized under the subgroup J01 under the anatomical and therapeutic classification (ATC) system) as a proxy. Between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
5
13
3
Order By: Relevance
“…Additionally, our study was more comprehensive, involving all health centers within the ERHA. Supporting our findings were studies from Europe, Africa and Asia, where penicillin and cephalosporin were found to be the highest consumed antibiotics [ 14 , 15 , 16 , 17 , 18 , 19 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, our study was more comprehensive, involving all health centers within the ERHA. Supporting our findings were studies from Europe, Africa and Asia, where penicillin and cephalosporin were found to be the highest consumed antibiotics [ 14 , 15 , 16 , 17 , 18 , 19 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…A study comparing antibiotic utilization among European Countries revealed an increase in antibiotic consumption by 36% from 2000 to 2010 [4]. In Sierra Leone, the total consumption of antimicrobials for the years 2017-2019 was 19 DDIs which is much lower than the rates found in our study [35].…”
Section: Discussioncontrasting
confidence: 82%
“…A study comparing antibiotics utilization among European countries revealed an increase in antibiotic consumption by 36% from 2000 to 2010 [4]. In Sierra Leone, the total consumption of antimicrobials for the years 2017-2019 was 19 DIDs, which was much lower than the rates found in our study [35]. The current increase may correspond to the scaling of health insurance in the country, which has increased clients' ability to access and purchase medicines [12,36].…”
Section: Discussioncontrasting
confidence: 72%